2010
DOI: 10.1097/aln.0b013e3181dfd401
|View full text |Cite
|
Sign up to set email alerts
|

Visual P2–N2 Complex and Arousal at the Time of Encoding Predict the Time Domain Characteristics of Amnesia for Multiple Intravenous Anesthetic Drugs in Humans

Abstract: Background-Intravenous anesthetics have marked effects on memory function, even at subclinical concentrations. Fundamental questions remain in characterizing anesthetic amnesia and identifying affected systems-level processes. We applied a mathematical model to evaluate timedomain components of anesthetic amnesia in human subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…Amnestic doses of midazolam or propofol, for example, allow a memory to be formed, which is rapidly lost over time (forgetting). [28][29][30] As the memory effect of amnestic drugs is changing rapidly during a 10-30 min period after encoding, subsequent recognition memory testing is best done beyond this time frame, and in current study was done after imaging and recovery from sedation. 29 31 Thus, amnesia in the sense of lack of memory for events occurring at drug concentrations causing little sedation, is most evident when drug concentrations are increasing slowly, or are held constant over increasing steps such as in studies using volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Amnestic doses of midazolam or propofol, for example, allow a memory to be formed, which is rapidly lost over time (forgetting). [28][29][30] As the memory effect of amnestic drugs is changing rapidly during a 10-30 min period after encoding, subsequent recognition memory testing is best done beyond this time frame, and in current study was done after imaging and recovery from sedation. 29 31 Thus, amnesia in the sense of lack of memory for events occurring at drug concentrations causing little sedation, is most evident when drug concentrations are increasing slowly, or are held constant over increasing steps such as in studies using volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ebert et al found suppression of recall and recognition memory after treating patients with sedative doses of DEX [4]. Further, DEX was reported to impair memory even at a low dose [5]. It is unclear how and where in the brain DEX acts to impair memory; however, a recent study using functional magnetic resonance imaging showed that DEX inhibits hippocampal activity in a region-specific fashion during learning [6].…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently Pryor et al modeled memory impairment induced by various intravenous drugs using a negative power function to separate drug actions on initial memory formation (encoding) from memory loss over time. 3 The question is how to refer to this latter effect, and that is the problem with "amnesia. "…”
mentioning
confidence: 99%
“…Propofol, having similar effects on memory as the benzodiazepines, is in many ways an ideal drug to study this peculiar effect on memory. 2,3 There is a crucial need to understand mechanisms underlying this effect, as lack of memory for intraoperative events is one of the key pillars of the triad (or pentad) of anesthesia.…”
mentioning
confidence: 99%